Influence of substrates, spawning and post-spawning practices on yield and yield attributing parameters of Indian oyster mushroom, Pleurotus pulmonarius - Hemalatha, P; Nayak, N; Mohapatra, K B; Chinara, N (Mushroom Research, 2018)
Nine agro-wastes including the paddy straw were evaluated for their influence on yield and yield attributing parameters of Pleurotus pulmonarius. A varying performance was observed among the substrates in respect of days to spawn run and fruit harvest, an average weight of sporophores and biological efficiency. The conventionally used substrate, paddy straw was found superior among the substrates in terms of fruit yield (99.30 %) followed by maize stalk (92.25 %), maize cob (91.93 %), green gram stick (88.27 %) and paddy husk (80.27 %). Sugarcane bagasse, coconut coir, rice bran and saw dust were proved to be the poor yielders with 61.07, 64.37, 70.20 and 77.40% biological efficiency. The superiority of paddy straw was established in terms of days to spawn run (16.33), days to first harvest (21.33) and the average weight of fruit bodies (10.71 g) among the substrates. Among the spawning methods followed, both layer spawning and through mixing ones were statistically at par yielding 97.66 and 96.87 % biological efficiency. However, the top spawning method was inferior in terms of yield (78.37 %). It was further observed that the yields obtained out of both uncovered bags (97.34 %) and the bags with 1.0 cm holes (96.47 %) were statistically at par with one another. Moreover, bags with smaller holes were comparatively poor yielders (91.68 %).